The Shakespearean forest - Barton, Anne 1933-2013 (Cambridge University Press, 2017)
Into the woods -- Staging the forest -- The wild man in the forest -- 'Like the old Robin Hood of England' -- The forest and the city -- Let the forest judge -- Afterword: Anne Barton (1933-2013) by Peter Holland
Keywords: Shakespeare, William -- 1564-1616; Geschichte 1580-1620; Wald -- Motiv; Englisch; Drama; Shakespeare, William, 1564-1616; Criticism and interpretation; Forests in literature